Dissolution of titanium dioxide nanoparticles in synthetic biological and environmental media to predict their biodurability and persistence. (October 2022) - Mbanga, Odwa; Cukrowska, Ewa; Gulumian, Mary
Abstract: Investigating the biodurability and persistence of titanium dioxide nanoparticles (TiO2 NPs) is of paramount importance because these parameters influence the particles' impact on human health and the environment. Contrary to most research conducted so far, the present study elucidates the dissolution kinetics, namely the dissolution rates, rate constants, order of reaction and half-times of TiO2 NPs in five different simulated biological fluids and two synthetic environmental media to predict their behaviour in real life situations. Results have shown that the dissolution of TiO2 NPs in all simulated fluids was limited. Of all the simulated biological media tested, acidic media such as phagolysosomal and gastric fluid produced the highest dissolution of TiO2 NPs compared to alkaline media such as blood plasma, Gamble's fluid, and intestinal fluid. Furthermore, when the particles were exposed to simulated environmental conditions, the dissolution was higher in high ionic strength seawater compared to freshwater. The dissolution kinetics of titanium dioxide nanoparticles followed first order reaction kinetics and were generally characterized by low dissolution rates and long half-times. These findings indicate that TiO2 NPs are very insoluble and will remain unchanged in the body and environment over long periods of time. Therefore, these particles are most likely to cause both short and long-term health effects and will remain persistent following release into the environment. Graphical abstract: Unlabelled Image Highlights: The dissolution of TiO2 NPs in all simulated fluids was limited. However, acidic media produced the highest dissolution compared to alkaline media. Titanium dioxide nanoparticles are insoluble and resistant to dissolution. Therefore, may cause long-term health effects and show high environmental persistency.